All Colour Book of Horses - Johnson, Elizabeth (London Octopus Books Ltd., 1972)
Profusely illustrated text describes the characteristics of various breeds of horses and discusses the ways they are used by people.
Includes Colored Illustrations.
Keywords: Horses -- Animals